Strip Clearcutting Drives Vegetation Diversity and Composition in the Moso Bamboo Forests. Issue 1 (14th December 2021) - Zheng, Yaxiong; Fan, Shaohui; Guan, Fengying; Xia, Wen; Wang, Shumei; Xiao, Xiao
Abstract: Strip clearcutting of Moso bamboo forests in southern China has seen increasing interest as a way of reducing harvesting costs. Previous research has shown that cutting influences the overstory structure and drives changes in the microclimate and soil properties. However, the effects of strip cutting on understory vegetation diversity and composition remain unclear. To better understand the influence of cutting on the understory vegetation, this study compares sites under natural restoration after cut and uncut sites in the Moso bamboo forest. We selected plots that were cut in 2019 (C19) and 2017 (C17), as well as unharvested plots as controls (CK). The results showed that strip clearcutting increased the understory vegetation richness and diversity, and a significant difference (A = 0.23, P = 0.001) existed in the composition of the vegetation between the three treatments. Furthermore, the decrease of soil total phosphorus and total potassium content resulted in the difference in undergrowth vegetation distribution and composition between the uncut plots and the cut plots. Our results suggest that strip clearcutting may not be harmful to biodiversity on a local scale in the Moso bamboo forest.